Chemical composition and antioxidant activity of the crude methanolic extracts of Mentha spicata - Rameshwar Naidu, J; Ismail, R B; Yeng, Chen; Sasidharan, S; P, Kumar (Journal of Phytology, 2012)
The chemical constituents and antioxidant activity of the crude extracts of Mentha spicata were investigated. Phytochemical analysis indicated the presence of sugar, flavonoids and alkaloids in the crude extracts of Mentha spicata. GC-TOFMS (Gas Chromatography Time-of-Flight Mass Spectrometry) analysis indicated the presence of fatty acid methyl esters (hexa decane, hepta decane, octa decane) terpenoids, terpenoid alcohol, caryophyllene and glycosides. Total phenolic components of the crude extracts was found to be 27.26±0.62 mg/g gallic acid equivalent which was determined by Folin-Ciocalteu method. The DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging activity was found to increase with increasing concentrations and was found to be 54.84±0.57% with an IC50 value of 25.2µg/ml. The reported antioxidant activity may be due to the presence of flavonoids and fatty acid methyl esters which has the scavenging potential by reducing the free radicals.